Influence of diapir structure on formation and distribution of overpressure in the Yinggehai Basin, South China Sea. Issue 7 (25th April 2022) - Huang, Honglin; Li, Jun; Yang, Hongwei; Zhang, Geng; Gao, Reyu; An, Jintao; Luo, Ming; Li, Wentuo
Abstract: The Yinggehai Basin (YGH) in the South China Sea is a Cenozoic, high‐temperature, and high‐pressure basin. Exploration and development of natural gas resources in the YGH show that owing to the diapir structures make the formation pressure system is complex, overpressure characteristics are obvious, prediction is difficult, and spatial distribution is irregular, which severely restricts the development of natural gas. To evaluate the influence of diapir structures on the formation and distribution of overpressure, we compared and analyzed the ancient and modern geothermal temperatures, organic matter maturity, clay mineral evolution, burial depth, and pressure coefficient in the diapir and nondiapir zones of the YGH. The results showed that of the diapir structures in the YGH occurred in the following order: Uplift–spiking–piercing–depositing. The Dongfang area is dominated by low‐amplitude turtle‐back diapir structures with weak energy, whereas the Ledong area is dominated by high‐amplitude spiked diapir structures with strong energy, both of which pressurize the upper formation. The Changnan area is dominated by high‐amplitude pierced/depositing diapirs with strong energy, which can relieve pressure. The influence of the diapir and its associated structures on the formation of overpressure can be attributed to the transport of the diapir body and the associated fault‐fracture system and the local thermal effect caused by the upwelling of hot fluids. Under the influence of the diapir structure, the overpressure top surface of the basin was shallower. According to the degree of influence and intensity of the diapir structure, variations in formation pressure coefficient with depth can be divided into four evolution modes: constant pressure, slow pressurization, "Z" pressurization, and "S" pressurization types. This study provides some guidance and references for the identification and accurate prediction of the overpressure formation mechanism in basins containing diapirs, and helps in formulating efficient drilling and production plans. Abstract : In this study, based on the sedimentary evolution characteristics of Yinggehai Basin (YGH), we analyzed the formation and evolution process of the diapir structure and its associated structures in YGH, revealing the influence mechanism of the diapir structure on the formation and distribution of overpressure. Our study makes a significant contribution to the literature because the study results are expected to provide guidance and reference for the exploration direction of favorable areas for hydrocarbon accumulation, identification of basin overpressure formation mechanism, and prediction of overpressure in sedimentary basins developing diapir structure.